2010
DOI: 10.1142/s0192415x10008391
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Gallate Inhibits the Production of Interleukin-6 and Nitric Oxide via Down-Regulation of Extracellular-Signal Regulated Protein Kinase in RAW 264.7 Cells

Abstract: To determine the anti-inflammatory and analgesic activities of methyl gallate (MG) isolated from Galla Rhois, MG was studied in vivo for its analgesic activities using the writhing response in mice. Anti-inflammatory activity of MG was evaluated for NO and IL-6 production in RAW 264.7 cells. MG inhibited LPS-induced NO and IL-6 production. Consistent with these observations, the protein and mRNA expressions of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were inhibited by MG. Moreover, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…In addition to ethyl gallate, Galla Rhois contains several gallic acid-derived components possessing antibacterial (Choi et al, 2009) and antitumor properties . A recent study has demonstrated that methyl gallate derived from ethanol extract of Galla Rhois inhibits the production of nitric oxide and interleukin-6 (Chae et al, 2010), suggesting that methyl gallate from Galla Rhois possesses potent anti-inflammatory activities. It would be interesting to investigate the inhibitory effect of ethyl gallate and methyl gallate on the inflammatory responses, which gives us valuable information about what component from Galla Rhois would be more effective for the treatment of inflammation-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ethyl gallate, Galla Rhois contains several gallic acid-derived components possessing antibacterial (Choi et al, 2009) and antitumor properties . A recent study has demonstrated that methyl gallate derived from ethanol extract of Galla Rhois inhibits the production of nitric oxide and interleukin-6 (Chae et al, 2010), suggesting that methyl gallate from Galla Rhois possesses potent anti-inflammatory activities. It would be interesting to investigate the inhibitory effect of ethyl gallate and methyl gallate on the inflammatory responses, which gives us valuable information about what component from Galla Rhois would be more effective for the treatment of inflammation-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a phytochemical and polyphenolic compound that is widely believed to have medicinal properties such as antioxidant [19], antitumor [20], anti-inflammatory [21], and antimicrobial [22]. In addition, it has been proven that methyl gallate acts as a potent inhibitor of sodium and potassium channels in skeletal muscle cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, administration of gallic acid to rats (Mohamed & Abd El‐Twab, ) and mice (Pandurangan et al, ) caused inhibition of iNOS expression and decreased NO levels, which is accompanied by free radical scavenging activity (Rajan & Muraleedharan, ). In other reports concerning different gallic acid glycosides, it was shown that propyl gallate inhibited the expression of iNOS in rats (Zheng et al, ), and methyl gallate inhibited NO production and iNOS expression (Chae et al, ; Correa et al, ). In addition, it has been proposed that gallic acid has anticancerogenic activity through different mechanisms (Subramanian et al, ).…”
Section: Resultsmentioning
confidence: 87%